Molecular studies of genomic imprinting using an Angelman syndrome imprinting defect mouse model - Hou, Aihua (2008)
Prader-Willi syndrome (PWS) and Angelman syndrome (AS) are distinct neurobehavioral disorders associated with the loss of paternally or maternally expressed imprinting genes within human chromosome 15q11-q13, respectively. The human PWS/AS imprinting domain is under the control of a bipartite imprinting center (IC). To dissect the molecular mechanisms of genomic imprinting concerning AS-IC, an AS-ICan mouse line made with 6 kb duplication and an insertion of puromycin driven by PGK promoter has been investigated. It was found that maternal inheritance of the AS-ICan mutation causes AS imprinting defect with incompelete penetrance in the 129/SvEv mouse strain and 129/PWK hybrid. In AS-ICan imprinting defect mice, the differential methylation region (DMR) of Snurf-Snrpn is biallelically unmethylated and the Snurf-Snrpn gene is biallelically expressed; moreover, the normally silent Ube3a-ATS maternal allele is activated, resulting in maternal Ube3a silencing. Chromatin immunoprecipitation (ChIP) assay demonstrates that histone H3K4 dimethylation is enriched from both parental alleles, and the enrichment of trimethyl H3K9 from maternal allele is reduced in AS-ICan imprinting defect mice when compared to wild type mice. The differential replication timing of PWS/AS domain is reduced in AS-ICan imprinting defect mice. A paternal-specific physical interaction between PWS-IC and Ndn gene is detected in wild type mice. Interestingly, the interaction is detected from both parental alleles in AS-ICan imprinting defect mice. The physical interaction of PWS-IC and NDN is also detected in human cell lines providing evidences for a new and evolutionarily conserved imprinting regulation mechanism for the PWS/AS imprinting domain. The inserted puromycin gene of the targeting vector only expresses from the cerebellum of AS-ICan imprinting defect mice, even though cerebellum and liver cells have the same DNA methylation and histone modification patterns. A new targeting vector has been constructed to further elucidate the mechanism. In summary, this study indicates that the expression of a maternally inherited PGK promoter upstream of Snurf-Snrpn causes DNA demethylation, histone H3K4 dimethylation, DNA looping, losing of replication timing delay, and activating normally silent paternally expressed genes, thus leading to AS imprinting defect.